The CURE assessment landscape from the instructor’s point of view: knowledge and skills assessments are highly valued support tools for CURE adoption - Kleinschmit, Adam J.; Govindan, Brinda; Larson, Jennifer R.; Qureshi, Amber A.; Bascom-Slack, Carol (Frontiers in Education, 2023)
Course-based undergraduate research experiences (CUREs) are a high-impact educational practice that engage students with authentic research in the classroom. CURE development models include those designed and implemented at an individual institution to wide-reaching multi-institutional network CUREs. The latter have lowered barriers to implementation by providing a centralized support system, centralized training and curricula, and mentoring. CURE learning outcomes span the three domains of learning: knowledge, skills, and attitude, while assessment of these domains can serve a variety of purposes to a collection of different stakeholders. To better understand the CURE assessment landscape from the instructor's point of view we surveyed instructors from an established network CURE. We found that these instructors overwhelmingly prefer use of knowledge and skillsbased over attitudinal CURE assessment instruments. The responding instructors value knowledge and skills assessment data for a particular CURE when deciding on whether to adopt and for highlighting student weaknesses that can be used to improve CURE instruction. CURE learning models have pointed towards use of generalizable instruments for measuring CURE outcomes, but since knowledge and skills assessments are typically CURE specific, obtaining funds for their developments may not be realistic. To address this concern, we outline a CURE network stakeholder co-design process for developing and validating a knowledge and skills assessment instrument without external support or a sizable time commitment. We encourage network CUREs to leverage